Pulse Profile Rule in Laser Heating of Opaque Targets in Air (Baghdad Science Journal, 2011)
A theoretical model is developed to determine time evolution of temperature at the surface of an opaque target placed in air for cases characterized by the formation of laser supported absorption waves (LSAW) plasmas. The model takes into account the power temporal variation throughout an incident laser pulse, (i.e. pulse shape, or simply: pulse profile).Three proposed profiles are employed and results are compared with the square pulse approximation of a constant power.